# Solving a System of Differential Equation by Finding Eigenvalues and Eigenvectors

## Problem 668

Consider the system of differential equations
\begin{align*}
\frac{\mathrm{d} x_1(t)}{\mathrm{d}t} & = 2 x_1(t) -x_2(t) -x_3(t)\\
\frac{\mathrm{d}x_2(t)}{\mathrm{d}t} & = -x_1(t)+2x_2(t) -x_3(t)\\
\frac{\mathrm{d}x_3(t)}{\mathrm{d}t} & = -x_1(t) -x_2(t) +2x_3(t)
\end{align*}

(a) Express the system in the matrix form.

(b) Find the general solution of the system.

(c) Find the solution of the system with the initial value $x_1=0, x_2=1, x_3=5$.

## Hint.

Use the following theorem.

Theorem.
Let $A$ be a diagonalizable $n\times n$ matrix.
Let $\{\mathbf{v}_1,\dots, \mathbf{v}_n\}$ be an eigenbasis for $A$, with associated eigenvalues $\lambda_1, \dots, \lambda_n$. Then the general solution of the linear dynamical system
$\frac{\mathrm{d}\mathbf{x}}{\mathrm{d}t} =A\mathbf{x}$ is
$\mathbf{x}(t)=c_1 e^{\lambda_1 t}\mathbf{v}_1+\cdots +c_n e^{\lambda_n t}\mathbf{v}_n,$ where $c_1, \dots, c_n$ are arbitrary complex numbers.

## Solution.

### (a) Express the system in the matrix form.

Writing
$\mathbf{x}=\begin{bmatrix} x_1 \\ x_2 \\ x_3 \end{bmatrix} \text{ and } A=\begin{bmatrix} 2 & -1 & -1 \\ -1 &2 &-1 \\ -1 & -1 & 2 \end{bmatrix},$ the system of differential equations can be written in the matrix form
$\frac{\mathrm{d}\mathbf{x}}{\mathrm{d}t} =A\mathbf{x}.$

### (b) Find the general solution of the system.

The eigenvalues of the matrix $A$ are $0$ and $3$. The eigenspaces are
$E_0=\Span \left(\, \begin{bmatrix} 1 \\ 1 \\ 1 \end{bmatrix} \,\right) \text{ and } E_3=\Span \left(\, \begin{bmatrix} -1 \\ 1 \\ 0 \end{bmatrix}, \begin{bmatrix} -1 \\ 0 \\ 1 \end{bmatrix} \,\right).$ (See the post “Quiz 13 (Part 1) Diagonalize a Matrix” for details.)

Thus, the formula in Theorem yields the general solution
\begin{align*}
\mathbf{x}(t)&=c_1 e^{0t}\begin{bmatrix}
1 \\
1 \\
1
\end{bmatrix}+c_2e^{3t}\begin{bmatrix}
-1 \\
1 \\
0
\end{bmatrix}+c_3e^{3t}\begin{bmatrix}
-1 \\
0 \\
1
\end{bmatrix}\6pt] &= c_1 \begin{bmatrix} 1 \\ 1 \\ 1 \end{bmatrix}+c_2e^{3t}\begin{bmatrix} -1 \\ 1 \\ 0 \end{bmatrix}+c_3e^{3t}\begin{bmatrix} -1 \\ 0 \\ 1 \end{bmatrix}, \tag{*} \end{align*} where c_1, c_2, c_3 are arbitrary constants. Equivalently, one may write the solution as a single vector \[ \mathbf{x}(t)=\begin{bmatrix} c_1-e^{3t}(c_2+c_3) \\ c_1+c_2e^{3t} \\ c_1+c_3e^{3t} \end{bmatrix}.

### (c) Find the solution of the system with the initial value $x_1=0, x_2=1, x_3=5$.

Substituting $t=0$ in the solution (*) obtained in part (b) yields
$\begin{bmatrix} 0 \\ 1 \\ 5 \end{bmatrix}=\mathbf{x}(0)=c_1 \begin{bmatrix} 1 \\ 1 \\ 1 \end{bmatrix}+c_2\begin{bmatrix} -1 \\ 1 \\ 0 \end{bmatrix}+c_3\begin{bmatrix} -1 \\ 0 \\ 1 \end{bmatrix}.$ Solving this system gives $c_1=2, c_2=-1, c_3=3$.
Thus, the solution of the system of differential equations with the given initial value is
$\mathbf{x}(t)=2\begin{bmatrix} 1 \\ 1 \\ 1 \end{bmatrix}-e^{3t}\begin{bmatrix} -1 \\ 1 \\ 0 \end{bmatrix}+3e^{3t}\begin{bmatrix} -1 \\ 0 \\ 1 \end{bmatrix}.$ Or equivalently,
$\mathbf{x}(t)=\begin{bmatrix} 2-2e^{3t} \\ 2-e^{3t} \\ 2+3e^{3t} \end{bmatrix}.$

##### Solve the Linear Dynamical System $\frac{\mathrm{d}\mathbf{x}}{\mathrm{d}t} =A\mathbf{x}$ by Diagonalization
(a) Find all solutions of the linear dynamical system $\frac{\mathrm{d}\mathbf{x}}{\mathrm{d}t} =\begin{bmatrix} 1 & 0\\ 0& 3 \end{bmatrix}\mathbf{x},$ where \$\mathbf{x}(t)=\mathbf{x}=\begin{bmatrix} x_1...